Homo- and Heterogeneous Benzyl Alcohol Catalytic Oxidation Promoted by Mononuclear Copper(II) Complexes: The Influence of the Ligand upon Product Conversion - Chimilouski L.* (2024)
© 2024 by the authors.The catalytic properties of three copper complexes, [Cu(en)2](ClO4)2 (1), [Cu(amp)2](ClO4)2, (2) and [Cu(bpy)2](ClO4)2 (3) (where en = ethylenediamine, amp = 2-aminomethylpyridine and bpy = 2,2′-bipyridine), were explored upon the oxidation of benzyl alcohol (BnOH). Maximized conversions of the substrates to their respective products were obtained using a multivariate analysis approach, a powerful tool that allowed multiple variables to be optimized simultaneously, thus creating a more economical, fast and effective technique. Considering the studies in a fluid solution (homogeneous), all complexes strongly depended on the amount of the oxidizing agent (H2O2), followed by the catalyst load. In contrast, time seemed to be statistically less relevant for complexes 1 and 3 and not relevant for 2. All complexes showed high selectivity in their optimized conditions, and only benzaldehyde (BA) was obtained as a viable product. Quantitatively, the catalytic activity observed was 3 > 2 > 1, which is related to the π-acceptor character of the ligands employed in the study. Density functional theory (DFT) studies could corroborate this feature by correlating the geometric index for square pyramid Cu(II)-OOH species, which should be generated in the solution during the catalytic process. Complex 3 was successfully immobilized in silica-coated magnetic nanoparticles (Fe3O4@SiO2), and its oxidative activity was evaluated through heterogenous catalysis assays. Substrate conversion promoted by 3-Fe3O4@SiO2 generated only BA as a viable product, and the supported catalyst’s recyclability was proven. Reduced catalytic conversions in the presence of the radical scavenger (2,2,6,6-tetrametil-piperidi-1-nil)oxil (TEMPO) indicate that radical and non-radical mechanisms are involved.